Environmental-Interaction Robotic Systems: Compliant Actuation Approach - Qiong Wu; Reza Ghorbani (International Journal of Advanced Robotic Systems, 2008)
Many successful designs of compliant actuators have been recently proposed. However, the challenge of providing passive and active motion in one actuator has remained. In this paper, a novel mechanism for changing the stiffness of the series elastic actuator over a wide range is presented. An accurate force source is provided by introducing the force control using velocity control of the DC motor. Performance and behaviour of the system and controller is investigated through simulation.